Effect of surface modification on mechanical properties of buri palm (Corypha Utan) fibre composite reinforcement - M., Zalinawati; Siregar, J. P.; Tezara, C.; Jaafar, J.; M. H. M., Hamdan; Oumer, A. N.; T., Rihayat (Universiti Malaysia Pahang, 2020)
Natural fibre materials are replacing synthetic fibre materials since they are considered as a low-cost, lightweight, and biodegradability engineering materials with a good specific strength. However, the effects of some process and geometrical parameters (such as fibre type, size, and concentration, and chemical modification) on the strength of the final natural composite product are not well documented. The purpose of the research is to analyse the physical and mechanical properties of single-strand buri palm fibre under different conditions and surface modification. The buri palm fibre was treated using 5 wt.% and 10 wt.% sodium hydroxide (NaOH) with a duration of 1 and 24 h immersion throughout the whole process. For a single-strand test, the samples were carefully extracted from the corresponding woven fibre by hand. While the woven buri palm fibre composite was fabricated by employing 4 and 5-layering sequences in the hand lay-up technique followed by the compression method. The buri palm fibre showed that a higher concentration of NaOH solution and immersion period led to a lower density. The effectiveness of the alkali treatment in the removal of cellulose and hemicellulose from the fibre strands was verified by chemical composition in FTIR investigation. The highest tensile strength of 159.16 MPa was indicated from the result of single-strand treated with 5 wt.% NaOH for 24 h immersion. This treatment was found as the most appropriate treatment and is employed to fabricate both 4-layer and 5-layer stacking sequence composite. The 5-layer treated composite gives the highest tensile strength and flexural strength of 33.51 MPa and 56.72 MPa, respectively. In conclusion, the mechanical properties increased with the addition of each sequence layering treated fibres in the composite. The obtained results indicate that the utilisation of buri palm fibre as a reinforcement in the epoxy composite can be used in the lightweight and moderate load applications, such as the interior parts in the automotive industry.